Controversy over Religious Court Decisions Regarding Marriage Isbat Laws - Razak, Dudung Abdul; Deski, Ahmad; Nashir, M.; Samsurizal, Samsurizal (Samara: Journal of Islamic Law and Family Studies, 2023)
Controversy in religious court decisions regarding marriage itsbat laws is a complex discussion in the context of Islamic law. Itsbat nikah, the process of legalizing marriage in the religious realm, is often a source of disagreement between the parties involved. This research aims to find out the decision of the religious court regarding the law on marriage itsbats. This research uses library research, collecting books and writings that are directly or directly related to the issues above. After the data is collected, classification analysis is then carried out using deductive methods to reach conclusions. Isbat nikah is a request for validation submitted to the Religious Court to declare the marriage valid so that it has legal force. Reasons for submitting a marriage itsbat in KHI Article 7 paragraph 3: The existence of a marriage in the context of settlement, the loss of a marriage certificate, the existence of a marriage that occurred before the enactment of Marriage Law No. 1 of 1974, a marriage carried out by those who do not have obstacles to marriage according to Law No. 1 of 1974. People who have the right to apply for a marriage itsbat in KHI Article 7 paragraph 4, namely husband, wife, their children, and parties who have an interest in the marriage. The urgency of the marriage Itsbat Provides a guarantee of legal certainty for every marriage and provides a guarantee of legal protection for the offspring of each couple. Marriage applications itsbat are made at the Religious Court at the place of domicile of the couple who will carry out their marriage itsbat.